Some Extralingual Variables of L2 Phonic Competence - Kralova, Zdena; Skorvagova, Eva; Ruttkay, Juraj (Communications - Scientific Letters of the University of Zilina, 2009)
The study assessed the relation between the overall degree of perceived foreign accent in non-natives' English speech and some extralingual factors. These variables include musical ability, phonic mimicry ability and type of personality. Five native speakers of English were asked to auditorily evaluate the samples of free English speech produced by each of 79 non-native talkers using the equal-appearing interval scale. The 5-point scale was used to rate each of the variables for each non-native speaker and the interclass correlation coefficients were calculated to identify the most important predictors of L2 pronunciation quality. The findings reported may be important for the learning and teaching second languages.
Keywords: no keywords